The effects of rope training on heart rate, anaerobic power and reaction time of the basketball players - Orhan, Serdar (My University, 2013)
A total of 40 men's basketball players, ranging from ages between 16-19, who played basketball at least for 3 years and struggling in young teams level, participated in this study in order to investigate the effects of rope training on the heart rate, anaerobic power, and reaction time. The basketball players were divided into two groups of experimental (n = 20) and control (n = 20) groups by a random method. Along with the training program, a technical training was also applied during a period of 8 weeks to the experimental group after 1 week preparatory rope training, consisting of weekly 3 days rope jumping. And to the control group was applied only a technical training of weekly 3 days during 8 weeks. Age, basketball age, height, body weight, the number of resting heart rate and immediately after the rope training number of heart rate, anaerobic peak and average power and right and left hand auditory and visual reaction times were measured in experimental and control groups. The statistical analysis of the data obtained was made in the package program, normally distributed data in the Simple Paired T-test, and for the data with abnormal distribution Wilcoxon and Mann-Whitney U tests were performed with a significance level of 0.05 in the dependent and the independent groups. As a result, it can be said that the rope trainings applied to the basketball players with explosive pace and re-applied method are effective on the heart rate and the anaerobic characteristics, whereas they do not effect the visual and the auditory reaction time.
Keywords: Anaerobic; Basketball; Reaction Time; Rope Training